Direct measurement of local constitutive relations, at the micrometre scale, in bulk metallic alloys. Issue 3 (1st June 2017) - Plancher, E.; Favier, V.; Maurice, C.; Bosso, E.; Rupin, N.; Stodolna, J.; Loisnard, D.; Marijon, J.-B.; Petit, J.; Micha, J.-S.; Robach, O.; Castelnau, O.
Abstract : The local mechanical behavior of a bulk stainless steel crystal is measured directly, at the micrometre scale, by combining total strain measurements with elastic strain measurements. Abstract : Multiscale models involving crystal plasticity are essential to predict the elastoplastic behavior of structural materials with respect to their microstructure. However, those models are often limited by a poor knowledge of the local constitutive behavior. This article reports a method to measure the mechanical behavior directly, at the micrometre scale, in bulk crystalline materials. Local strain and stress states were evaluated at the surface of a bent stainless steel crystal by combining total strain measurements – performed with the digital image correlation technique on optical images – with elastic strain measurements obtained by Laue microdiffraction. A local constitutive relation was measured, in an efficient nondestructive way, without the need for full‐field simulations. The method was validated by a comparison between the measured local behavior and the macroscopic behavior of the single crystal.